2019
DOI: 10.1111/jvh.13168
|View full text |Cite
|
Sign up to set email alerts
|

GWAS identifying HLA‐DPB1 gene variants associated with responsiveness to hepatitis B virus vaccination in Koreans: Independent association of HLA‐DPB1*04:02 possessing rs1042169 G ‐ rs9277355 C ‐ rs9277356 A

Abstract: Recently, HLA class II loci, including HLA-DPB1, have been reported to be associated with interindividual variance in the hepatitis B (HB) vaccine response. In this study, we investigated significant single nucleotide polymorphisms (SNPs) for anti-HBs antibody levels in 6867 healthy Koreans using a genome-wide association study (GWAS).In GWAS, the top 20 SNPs that showed significant association with anti-HBs levels (P < 1.0 × 10 −29 ) all resided in HLA-DPB1. Utilizing PCR sequencing, we verified the relations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 42 publications
1
12
0
Order By: Relevance
“…Ragone et al. found HLA did not impact on short-medium-term antibody response to Pfizer-BioNTech BNT162b2 vaccine, which was a SARS-CoV-2 mRNA vaccine ( 36 ), though HLA variants have been shown to be associated with antibody response to several other pathogen vaccines ( 15 18 , 37 39 ). Consistent of this research, we did not found associations between HLA variants and antibody response either.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ragone et al. found HLA did not impact on short-medium-term antibody response to Pfizer-BioNTech BNT162b2 vaccine, which was a SARS-CoV-2 mRNA vaccine ( 36 ), though HLA variants have been shown to be associated with antibody response to several other pathogen vaccines ( 15 18 , 37 39 ). Consistent of this research, we did not found associations between HLA variants and antibody response either.…”
Section: Discussionmentioning
confidence: 99%
“…Human genetic background has been suggested to contribute to inter-individual difference in antibody response to many vaccines ( 13 , 14 ). For example, multiple studies revealed HLA variants were associated with antibody response to hepatitis B vaccine ( 15 18 ). CD46 and IFI44L genetic variants were revealed to be associated with neutralizing antibody response to measles vaccine ( 19 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, to our knowledge, very few studies have been published reporting genetic associations with reactogenicity after non live-attenuated vaccines. In the past, a few studies have investigated the genetics of response to vaccines by looking at the levels of antibodies after a certain time period in vaccine recipients, often identifying associations with HLA genes 15,16 . Other studies have elucidated why some patients presented with a rare life-threatening disease following vaccinations with live-attenuated vaccines 17 .…”
Section: Discussionmentioning
confidence: 99%
“…However, despite the continuously growing number of vaccine-associated GWASs, these studies are either clustered within specific ethnic groups, or focused on a limited number of pathogens. Most of the currently available reports are on vaccine response to hepatitis B, measles, rubella, influenza A, smallpox, anthrax, and mumps (4,5,7,(25)(26)(27)(28)(29).…”
Section: Genome-wide Association Studiesmentioning
confidence: 99%
“…The most significant associations were linked to HLA polymorphisms. Multiple HLA alleles were associated with anti-hepatitis surface antigen IgG levels including HLA-DPB1 and HLA-DRAB5 and HLA-DQA1 (5,(25)(26)(27). HLA genes are known to be the most polymorphic region of human genes, and encodes surface proteins which are essential in self and non-self-antigen presentation (37).…”
Section: Genome-wide Association Studiesmentioning
confidence: 99%